Analyzing the Expectations of the Old Aged People Using Fuzzy Model - A. Victor Devadoss; A. Lincy Amala Celine (International Journal of Mathematics And its Applications, 2017)
The advancement of technology and the necessities of the day to day life force the children to leave their parents to the old aged homes. Due to this process, the mushroom growths of old aged homes exist. And how far this home for aged satisfies the expectations of the parents and the responsibilities of the children are of major concern. The expectations of the elderly are very simple but not all children realize their importance or value their presence in their lives. The varying degree of acceptance of their ageing parents according to the human values is a valid criterion to study the expectations of the old aged people. The fuzzy logic serves as an appropriate tool to study the expectations as it is an unsupervised data. The problem of study is analyzed using the appropriate fuzzy model in this paper. The section one is of introductory nature. The second section gives the introduction to triangular fuzzy cognitive maps. The description of the problem is given in section three; and in the fourth section the model is adapted to the problem of study. The conclusion is derived in the final section.